Build a strong AngularJS foundation / by Lukas Ruebbelke and Matias Niemelä. - Ruebbelke, Lukas (O'Reilly, 2014)
"Ready to dig into web application development with AngularJS, but not sure where to start? With this video course, you'll learn how the framework's foundational building blocks work together for constructing sophisticated web apps. You'll learn each core concept separately with practical examples, live code demonstrations, and hands-on exercises."--Resource description page.